Numerical analysis of complex heat storage unit during freezing of phase change material enhanced withTiO2 nanoparticles. (15th November 2022) - Feng, Yipeng; Qin, Yinghong
Abstract: Improvement of discharging process of system with inclusion of nanoparticles (TiO2 ) and install of new style of fins have been illustrated in this investigation. The scrutinized paraffin (n-eicosane) become solidify at 309 K and fraction of nanoparticles is less than 0.03 for all cases which is permission of using homogeneous model for estimating properties. Although the efficacy of gravity force can be neglected in freezing, in current modeling, the related term has been applied and contours for velocity have been reported. The outer wall of tank has square shape and zero gradient condition was applied for that wall. The circular wall which the fins attached to this has cold wall (296 K). Thus, appearance of fins makes the freezing faster. Number of fins ( n = 1, 3, 7) and fraction of TiO2 (ϕ = 0, 0.03) were the variables of simulations. With adding nano-powders, the required time declines about 3.33 %, 2.69 % and 2.015 % when n = 1, 3 and 7, respectively. Increasing number of fins from 1 to 3 and 7, makes freezing time to decline around 23.24 % and 28.41 %. Highlights: Discharging process of system with inclusion of nanoparticles is studied. Buoyancy effect was involved for freezing process. With adding nano-powders, the required time declines about 3.33 %. Increasing number of fins makes freezing time to decline around 28.41 %.